RORC overexpression as a sign of Th17 lymphocytes accumulation in multiple myeloma bone marrow. (October 2020) - Ben Hmid, Ahlem; Selmi, Oumayma; Rekik, Raja; Lamari, Hajer; Zamali, Imen; Ladeb, Saloua; Safra, Ines; Ben Othman, Tarek; Ben Romdhane, Neila; Ben Ahmed, Melika
Abstract: The role of the bone marrow microenvironment in supporting the proliferation and survival of the abnormal plasma cells in multiple myeloma (MM) is well established. Such microenvironment is rich of cytokines like IL-6, TGF-β, IL-1 and IL-23 which are known to promote the differentiation of Th17 lymphocytes, a T helper subpopulation. Th17 cells secrete IL-17, a cytokine involved in the pathophysiology of several auto-immune diseases. Yet, its involvement in cancers remains unclear. Herein, we aimed to try to understand the role of Th17 lymphocytes in multiple myeloma. Bone marrow samples were prospectively collected from 29 MM patients and 23 healthy bone marrow donors for allograft. Mononuclear bone marrow cells were isolated by Ficoll-Hypaque gradient and CD138 + plasma cells were depleted using magnetic beads. The quantification of Th17 cells was performed by flow cytometry in the CD138 negative cells. The mRNA expression of IL17 and RORc was quantified using real time PCR in the same subset. The mRNA expression of IL17R was analyzed in plasma cells (CD138 + cells). Data obtained from patients and healthy donors were compared by both non-parametric Mann-Whitney U test and Spearman test. A significant increase of IL17 and RORC mRNA expression was found in the bone marrow microenvironment of MM patients compared to healthy donors. Th17 cells were also increased in the bone marrow of MM patients compared to healthy donors. Interestingly, the mRNA expression of IL17R was significantly decreased in MM patients. Yet, no correlation was found between the gene expression IL17, RORC and IL17R and the bone marrow infiltration or the stage of the disease. Collectively, our results suggest the involvement of Th17 cells in the pathophysiology of MM. Such data further support the use of anti-IL-17 antibodies as a therapeutic approach in MM.